2004
DOI: 10.1074/jbc.m313796200
|View full text |Cite
|
Sign up to set email alerts
|

Salicylihalamide A Inhibits the V0 Sector of the V-ATPase through a Mechanism Distinct from Bafilomycin A1

Abstract: The newly identified specific V-ATPase inhibitor, salicylihalamide A, is distinct from any previously identified V-ATPase inhibitors in that it inhibits only mammalian V-ATPases, but not those from yeast or other fungi (Boyd, M. R., Farina, C., Belfiore, P., Gagliardi, S., Kim Acidification of intracellular compartments of eukaryotes is essential for many cellular processes, including receptor-mediated endocytosis, protein degradation in lysosomes, processing of hormones, uptake, and storage of neurotransmitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 38 publications
7
107
0
Order By: Relevance
“…The rapid reduction in synaptic responses seen after folimycin treatment was only weakly reversible, even after extended wash out and stimulation (data not shown) (Xie et al, 2004). This shortcoming prompted us to explore an alternative reversible means to impair neurotransmitter refilling and assess the kinetics of synaptic vesicle reuse.…”
Section: Frequency-dependent Augmentation Of Synaptic Depression By Smentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid reduction in synaptic responses seen after folimycin treatment was only weakly reversible, even after extended wash out and stimulation (data not shown) (Xie et al, 2004). This shortcoming prompted us to explore an alternative reversible means to impair neurotransmitter refilling and assess the kinetics of synaptic vesicle reuse.…”
Section: Frequency-dependent Augmentation Of Synaptic Depression By Smentioning
confidence: 99%
“…In the next set of experiments, we used another high affinity v-ATPase inhibitor, salicylihalamide A, to test the specificity of the folimycin effect (Xie et al, 2004). Treatment of hippocampal slices with salicylihalamide A (10 nM) resulted in a similar frequency-dependent augmentation of synaptic depression (Fig.…”
Section: Salicylihalamide a Mimics The Effect Of Folimycinmentioning
confidence: 99%
“…In cell tests, all of these substances exhibited IC 50 values in the nanomolar range (Erickson et al, 1997;Huss et al, 2005;Kim et al, 1999;Kunze et al, 1998;McKee et al, 1998) and in the NCI 60-Cell screen, all of them revealed a V-ATPase inhibitor pattern similar to that of the plecomacrolides ) (Brigitte Kunze, personal communication). Assays of their inhibitory specificity for the VATPase carried out with either membrane preparations of human kidney, liver, osteoclast or bovine chromaffin granules Shen et al, 2002), or with purified V-ATPase from insect midgut (Huss et al, 2002;Huss et al, 2005) or bovine clathrin coated vesicles (Xie et al, 2004) clearly showed that the benzolactone enamides are indeed a novel family of highly specific V-ATPase inhibitors, with IC 50 values in the nanomolar range. One of the most astonishing and interesting features of the benzolacton enamides is that they do not inhibit V-ATPases from fungal sources, as was shown so far for salicylihalamide, lobatamides and oximidines with preparations of vacuolar membranes from N. crassa and Streptomyces cerevisiae , and for apicularen with preparations of vacuolar membranes from S. cerevisiae (S. Bockelmann, M.H., B. Kunze and H.W., unpublished results).…”
Section: Benzolactone Enamidesmentioning
confidence: 99%
“…4,10,11 This class of inhibitors includes the lobatomides and salicylihalamides, which were isolated from the marine tunicate worm 12 and marine sponge, 13 respectively and were originally identified as antitumor compounds. 10 Salicylihalamides bind to the V0 complex of the mammalian vATPase and this binding is distinct from the binding site for bafilomycin 14 and concanamycin. 4 In a previous study we showed that treatment of pancreatic acinar cells with bafilomycin or concanamycin blocked cerulein (CER)-induced zymogen activation.…”
Section: Dovepressmentioning
confidence: 99%